Lactobacillus gasseri LGV03 isolated from the cervico-vagina of HPV-cleared women modulates epithelial innate immune responses and suppresses the growth of HPV-positive human cervical cancer cells - Qiong Gao; Tao Fan; Siying Luo; Jieting Zheng; Lin Zhang; Longbing Cao; Zikang Zhang; Li Li; Zhu Huang; Huifen Zhang; Liuxuan Huang; Qing Xiao; et al. (Translational Oncology, 2023)
Persistent human papillomavirus (HPV) infections is necessary for the development of cervical cancers. An increasing number of retrospective studies have found the depletion of Lactobacillus microbiota in the cervico-vagina facilitate HPV infection and might be involved in viral persistence and cancer development. However, there have been no reports confirming the immunomodulatory effects of Lactobacillus microbiota isolated from cervico-vaginal samples of HPV clearance in women. Using cervico-vaginal samples from HPV persistent infection and clearance in women, this study investigated the local immune properties in cervical mucosa. As expected, type I interferons, such as IFN-α and IFN-β, and TLR3 globally downregulated in HPV+ persistence group. Luminex cytokine/chemokine panel analysis revealed that L. jannaschii LJV03, L. vaginalis LVV03, L. reuteri LRV03, and L. gasseri LGV03 isolated from cervicovaginal samples of HPV clearance in women altered the host's epithelial immune response, particularly L. gasseri LGV03. Furthermore, L. gasseri LGV03 enhanced the poly (I:C)-induced production of IFN by modulating the IRF3 pathway and attenuating poly (I:C)-induced production of proinflammatory mediators by regulating the NF-κB pathway in Ect1/E6E7 cells, indicating that L. gasseri LGV03 keeps the innate system alert to potential pathogens and reduces the inflammatory effects during persistent pathogen infection. L. gasseri LGV03 also markedly inhibited the proliferation of Ect1/E6E7 cells in a zebrafish xenograft model, which may be attributed to an increased immune response mediated by L. gasseri LGV03.